Moon 250,000 miles from home, the hardest thing to face ... is yourself - Jones, Duncan Zowie Hayward 1971-; Rockwell, Sam 1968- (Sony Pictures Home Entertainment, 2009)
Astronaut Sam Bell is completing a three-year contract with Lunar Industries to mine Earth's primary source of energy on the dark side of the moon: Helium-3. His declining health is causing headaches and hallucinations that lead to a near-fatal accident, rendering him unconscious. After recuperating, an unexpected discovery leads him to doubt his sanity, his identity, and the integrity of the company. Believing he is alone on his mission, his sole purpose is getting back home on his own.
Orig.: GB 2009. - Sprachen: Engl. - Untertitel: Engl. für Hörgeschädigte, Hindi
Keywords: Astronauts -- Drama; Discoveries in geography -- Drama; Hallucinations and illusions -- Drama; Headache -- Drama; Helium -- Drama; Mining engineering -- Drama; Moon -- Drama; Outer space -- Exploration -- Drama; Action and adventure films; Feature films; Fiction films; Science fiction films; Video recordings for the hearing impaired; Feature films - Great Britain